Servant leadership in the context of Mosque: A qualitative case study of Muslim women's perspectives - Sami Jabarkhail (Administrative Sciences, 2020)
This research provides an exploratory analysis of how Muslim women perceive servant leadership in the context of Mosque. The study consists of 8 long interviews with Muslim women, and conceptualizes sources of servant leadership in the context of Mosque by investigating Muslim women's perceptions of the Imam's leadership style The emerging taxonomy illuminates five categories and fifteen sub-categories of Muslim women's perceived servant leadership origin, relating to the impact Imam and Mosque have on: (1) Serviceability, (2) masculinity, (3) community, (4) accessibility, and (5) inclusivity. Findings show disparities between women and men and demonstrate the fact that Muslim women do benefit from Imam's leadership, services, and resources offered in Mosque; however, the benefits to women are disproportionate and different from men. In addition to making a vital contribution to the scarce literature on Muslim women's perspectives, this article provides stakeholders with a comprehensive set of issues which may evoke favorable/unfavorable perceptions and offers insight to direct improvement efforts in addressing these issues.
Keywords: 350; servant leadership; Imam; Mosque; wellbeing